In order to find the quadratic equation, let's use the vertex form below:
![y=a(x-h)^2+k](https://img.qammunity.org/2023/formulas/mathematics/college/97p0xsjs0cwme4ddvwkim2cbbqprhnlhsv.png)
Where the vertex is located at (h, k).
So, if the vertex is (h, k) = (-4, 2) and using the point (x, y) = (-4, 0), we have:
![\begin{gathered} y=a(x+4)^2+2 \\ 0=a(-4+4)^2+2 \\ 0=a\cdot0^2+2 \\ 0=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/wdwkllz0y997ys3uvmzpi04i2o9vtp2iul.png)
Since the final statement is false, it's not possible to have a quadratic function with vertex (-4, 2) and with the point (-4, 0).
If we use the point (4, 0) instead, we would have:
![\begin{gathered} y=a(x+4)^2+2 \\ 0=a(4+4)^2+2 \\ 0=a\cdot64+2 \\ 64a=-2 \\ a=-(2)/(64) \\ a=-(1)/(32) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ifd7adil4yrmec1jgfd8r3sjxnedhr865d.png)
So the equation in this case would be:
![y=(-(1)/(32))(x-(-4))^2+2](https://img.qammunity.org/2023/formulas/mathematics/high-school/x29f4mri565nfs8q5iuj3sfaoyk1bppb2q.png)
The empty spaces would be filled with the values -1/32, -4 and 2.